EMPLOYEE RELATIONS AND ITS IMPACT ON ORGANIZATIONAL PERFORMANCE (A STUDY OF ECOBANK PLC YOLA, ADAMAWA STATE, NIGERIA) - Ihentuge Achilike, Nicholas; Onyereibe Nwokeiwu, Johnson; Emeka Enujioke, Isaac (African Journal of Social and Behavioural Sciences, 2024)
This study focused on employee relationships and organisational performance: a case study of Ecobank Nig Plc. The study sought to investigate the relationship between employee relations and its effects on organisational performance. This study adopted a survey method using questionnaires as the instrument for data collection. Data were analysed using Pearson’s Moment correlations with the help of SPSS Social Science package version 21. Findings showed that healthy relationships have significant positive correlation with employee relationships (r = 1.00, p<.05). The promotion of effective communication among employees has a positive correlation with employee relationships (r = ‘396, p<.05). The application of emotional intelligence has a significant positive correlation with employee relationships (r = .686, p<.05). The ability to maintain harmonious relationships is very important for the survival, prosperity and growth of any business and creating good and healthy employee relationships lead to better performance. Focusing on building an effective and sustainable employee relationship is critical for the growth and realization of organizational objectives, creation of a convivial work environment and constant connection with employees enhances employees’ work performance. Furthermore, the creation of recreational activities for employees occasionally promotes serious bonds among employees. Finally, maintaining a positive attitude towards employees and maintaining effective communication channels encourage understanding and learning among employees.